International Dialogue: Our Experience in a Family Therapy Program - Mcdowell, Teresa; Fang, Shi-Ruei; Griggs, Julie; Speirs, Karl; Perumbilly, Sebastian; Kublay, Aliye Ebru (Journal of Systemic Therapies, 2006)
In this paper, we report our experiences as part of an international dialogue group within a U.S. family therapy training program. We describe the dialogue group and share the outcomes of our work together, including our understandings of how global relations, social positions, and personal/cultural characteristics influence our interactions within local contexts. We discuss how participation increased our international awareness and competence, offering two illustrations of how the group helped participants consider family therapy practice and research from a global perspective. Finally, we share the subjective experiences of student group members from the Southern United States, India, Turkey, and South Africa as testimony to the value of cross-national dialogue and to making space for affirming the unique journeys of international learners.
Keywords: dept.mft; peer-reviewed